Parental readiness, parental care, and adolescent school performance among commuter families in Malaysia: a mediation model - Siaw, Yan Li; Roslan, Samsilah; Abdullah, Maria Chong; Abdullah, Haslinda (IACSIT Press, 2014)
This study aimed (i) to examine the relationship between parental readiness, parental care, and adolescent school performance; and (ii) to test the role of parental care as mediator between parental readiness to commute and the adolescent school performance. Quantitative test was employed in this study, which included correlation study design and path analysis. Two sets of questionnaires were used to gather the information from adolescent (Parental Care) and parent (Parental Readiness) among the commuter families. However, the adolescent school performance provided by the school management. Pearson Correlation Test was first conducted to analyse the relationship between research variables and path analysis was that used to test the mediation effect. A total of 217 parent-adolescent (dyadic relationship) respondents from commuter families in Peninsular Malaysia were included in this study. The findings showed that all correlations were statistically significant and analysis of structural equation modeling revealed full mediation model of parental care between parental readiness and adolescent school performance. The total direct effect was 0.11; whilst the total indirect effect was 0.3213. This implicates the importance of mediation effect between parental readiness, parental care and adolescent school performance. To the best of our knowledge, this is the first study conducted in Malaysia to investigate the mediation effect on parental care between their readiness to commute against adolescent school performance. Our earlier study suggested a different lifestyle between commuter and conventional family model in Malaysia. Therefore, the importance of parental readiness and their roles in commuter families need to be addressed to ensure the lifestyle of commuter families in Malaysia do not affect adolescent school performance.